THE EFFECTIVENESS OF SELF-SELECTED READING TO IMPROVE STUDENTS’ READING COMPREHENSION IN EXTENSIVE READING COURSE - Fheby Indriyanti Nurpratiwi; Junita Siahaan; Reni Apriani (Esteem Journal of English Education Study Programme, 2025)
This study investigates the impact of Self-Selected Reading (SSR) on enhancing students’ reading comprehension within the Extensive Reading Course at La Tansa Mashiro University. Utilizing a Classroom Action Research (CAR) design, the research involved 20 undergraduate participants who engaged in interest-driven reading over two instructional cycles. Data were gathered through comprehension tests, classroom observations, and student reading logs, then analyzed using both qualitative and quantitative methods. Findings from the first cycle revealed that 62.5% of students demonstrated active engagement, yet only 35% achieved the benchmark score of 70 or higher. In contrast, the second cycle showed significant improvement, with 86.7% of students actively participating and 95% attaining the targeted comprehension score. These outcomes highlight a marked advancement in reading performance following the integration of SSR. The study concludes that embedding SSR into the Extensive Reading curriculum significantly enhances not only students’ reading proficiency but also cultivates a more positive disposition toward reading. It recommends that educators incorporate SSR to promote reading engagement and support the development of autonomous, motivated readers.